27Al MAS NMR investigations on Al23Te77 glass: Observation of 5- coordinated Al and its influence on electrical switching. (May 2019) - Wilson, P.T.; Chahal, Shweta; Pumlianmunga,; Madesh Kumar, M.; Ramesh, K.
Abstract: 27 Al Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR) spectroscopic studies show that Al resides in 4-, 5- and 6- fold coordination in bulk Al23 Te77 glass. Also, Al23 Te77 glass is found to exhibit threshold type switching. Earlier studies report memory type switching in Al-Te glasses wherein Al has been found only in [4] Al and [6] Al environments. X-Ray Photo Electron Spectroscopic (XPS) measurements show the presence of Al2 O3 in Al23 Te77 glass network. The structural network of Al-Te glass has been cross linked by the presence of higher coordinated Al atoms. The structural reorganization becomes difficult due to the increased network connectivity. Thus, the memory switching (which requires an easy structural reorganization) is retarded, resulting in the observation of threshold switching. Highlights: Al23 Te77 glass has been prepared by melt quenching under different pressures. 27 Al NMR spectrum shows 4-, 5- and 6- fold coordinated Al in Al23 Te77 glass. The influence of 5- fold coordinated Al on electrical switching has been studied. [5] Al facilitates the movement of Al so that threshold switching is observed. XPS measurements show oxidation of Al and the presence of Al2 O3 in the network.